Tingkat Kecemasan Ibu Rumah Tangga dengan HIV Positif di Kota Palangka Raya - Nurul Chusna; Nurhalina Nurhalina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
In Central Kalimantan, it is reported that the cumulative number of HIV and AIDS reached 810 people, with the highest proportion being housewives (19.4%). This number is even higher when compared with HIV / AIDS in Commercial Sex Workers (CSWs) which is 7.4%. For homemakers, the reality of getting HIV / AIDS is related to social construction in the community which places women as the second class, so stigmatization and discrimination often occur. Whereas in some cases for women housewives affected by HIV / AIDS having double burdens such as pregnancy, babies conceived are at risk of contracting HIV, caring for children, caring for a sick husband and sometimes being the backbone of the family because family expenses are increasing. Therefore in the HIV and AIDS control program, the anxiety level of HIV / AIDS patients is a bridge to control the complications of HIV/AIDS in the AIDS stage. Based on the description above, the researchers were interested in researching the anxiety level of HIV (+) homemakers in the City of Palangka Raya. The general objective of this study was to describe the anxiety level of HIV (+) homemakers in Palangka Raya City. This study uses a descriptive qualitative design. Qualitative research was used withconsideration of the focus of attention of researchers is the anxiety level of housewives with HIV/AIDS (+) in the City of Palangka Raya. The technique used in collecting research data is participant observation (participant observations) in-depth interviews and documentation. The implementation of the three data collection techniques is not rigid but sees the right situation. An illustration of the level of anxiety in HIV positive housewives who were respondents, it was found that respondents with mild anxiety levels were 9.5%, while those with moderate anxiety levels were 28.6%, respondents with severe anxiety levels were 38.1%, of which the highest percentage of respondents is at the level of severe anxiety, this is indicated by the results of the rate of respondents' answers, while the respondents with panic/severe anxiety levels were obtained as much as 23.8%. This was felt by respondents with a high level of anxiety, namely discomfort in the extended family, even though the husband could accept the situation but his extended family, in-laws, and siblings were unable to take the presence of HIV positive respondents.